Stunting Risk Factor in Toddlers 6-59 Months - Haniarti Haniarti; Fitriani Umar; Suci Triananda; Aldian Dani Anwar (Sarana Ilmu Indonesia (salnesia), 2022)
The number of toddlers experiencing stunting was still quite high and can have an impact on their growth and development. This study aims to analyzed the factors that influence the incidence of stunting in children aged 6-59 months in Parepare City. This type of research was observational with a cross-sectional study approach. The sample that became the subject of this study were children aged 6-59 months in Parepare city. Sampling was done by simple random sampling method as many as 49 people. Data were analysed using Chi-square test and Fisher Exact Test. The results showed that 49% of children under five were stunted. Birth length (p=0,425), low birth weight (p=1,000), mother's education (p=0,889), socioeconomic (p=0,667), age of complementary feeding (p=0,680) and type of food (p=0,951) were not significant effect on the incidence of stunting in children under five in the City of Parepare. It was suggested the need for education in increasing the knowledge of mothers of toddlers, especially in preparing first 1000 days of life .